2010
DOI: 10.2337/dc10-1124
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Shared Medical Record With Secure Messaging by Older Patients With Diabetes

Abstract: OBJECTIVEEvaluate use of a web-based shared medical record (SMR) between older patients with diabetes and providers.RESEARCH DESIGN AND METHODSThis was a retrospective cohort study. Health records and SMR use patterns of 6,185 enrollees aged ≥65 years with diabetes were analyzed from implementation of a SMR in August 2003 through December 2007. We analyzed baseline predictors of age, sex, distance from clinic, socioeconomic status, insulin use, morbidity, and associated primary care provider's (PCP) secure mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 16 publications
1
75
1
Order By: Relevance
“…Patients in our study who do use the patient portal are on average above 60 years old, which is higher than previously found. 19,20 This is in line with the increasing use of the Internet by the elderly in recent years. 37 Therefore we expect that in the near future this age gap will level off.…”
Section: Type 2 Diabetes Mellitussupporting
confidence: 63%
See 1 more Smart Citation
“…Patients in our study who do use the patient portal are on average above 60 years old, which is higher than previously found. 19,20 This is in line with the increasing use of the Internet by the elderly in recent years. 37 Therefore we expect that in the near future this age gap will level off.…”
Section: Type 2 Diabetes Mellitussupporting
confidence: 63%
“…17 However, other studies indicate that elderly patients with diabetes effectively use the Internet 19 and are interested in patient portals. 19,20 One of the limitations of the existing evidence is that most of the studies about patient portals have been conducted in the general population instead of in a population of only diabetes patients. 16, 21 The few studies carried out in a diabetes population did not differentiate between types of diabetes or treatment settings.…”
mentioning
confidence: 99%
“…A retrospective study of older patients with diabetes found that patients whose providers sent more electronic messages visited their patient portal more often 17. A literature review that investigated barriers to the use of interactive consumer HIT tools for patient who were older, underserved, or had chronic conditions found that active and timely interactions with clinicians increased patient satisfaction with HIT systems 5.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding variation in messaging usage between different patient populations could help health care organisations target promotional initiatives to improve adoption of messaging functionality. Few studies have specifically studied the characteristics of patients who use electronic patient-provider messaging systems and current studies lack diverse, urban populations 16,17. This study helps to fill these gaps by investigating the messaging usage of a demographically and socioeconomically diverse population of patients in New York City.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, work by investigators at Group Health, an integrated care system, has found high rates of use by patients with diabetes over age 65. 23 A key insight from this line of research is that one of the most important benefits of advanced patient portal tools is the ability to facilitate visitindependent communication between providers and patients.…”
Section: Personal Health Recordsmentioning
confidence: 99%